DOES EXPERIENCE, GENERALIZATION, REINFORCEMENT, AND APPLICATION (EGRA) EFFECTIVE IN COMPREHENDING RECOUNT TEXT? - Sholihatul Hamidah Daulay; Yani Lubis; Reflina3; Aula Adnin Ritonga (Yavana Bhasha : Journal of English Language Education, 2022)
The purpose of this study was to learn about the EGRA approach and how it affects students' capacity to grasp recount material in tenth grade. The study was a quantitative study using a quasi-experimental design that used a one-group pre-post test design. As the research sample, there was just one class with 31 pupils.The data was collected based on the students' pre- and post-test scores, and the data was calculated using SPSS 17.0 to assess data normality, homogeneity, and the hypothesis test. The Sig (2 tailed) of the pre-post test was less than the minimum value of significant (.000 0.05), or the tcount of the pre-post test was more than the ttable (11.4 > 2.04 with df 30 and sig. value 0.025) according to the SPSS computation.